Immune checkpoint inhibitor related nephrotoxicity: Advances in clinicopathologic features, noninvasive approaches, and therapeutic strategy and rechallenge - Miao, Jing; Sise, Meghan E.; Herrmann, Sandra M. (Frontiers in Nephrology, 2022)
Immune checkpoint inhibitors (ICIs) are used increasingly to treat more than 17 cancers and have shown promising therapeutic results. However, ICI use can result in a variety of immune-related adverse events (IRAEs) which can occur in any organ, including the kidneys. Acute kidney injury (AKI) is the most common nephrotoxicity, classically related to acute interstitial nephritis. Much more diverse patterns and presentations of ICI-related kidney injury can occur, and have implications for diagnostic and therapeutic management approaches. In this review, we summarize the recently approved ICIs for cancer, the incidence and risk factors for nephrotoxicity, our current understanding of the pathophysiological mechanisms and the key clinicopathological features of ICI-related AKI, and therapeutic strategies. We also explore important knowledge that require further investigation, such as the risks/benefits of ICI rechallenge in patients who recover from an episode of ICI-related AKI, and the application of liquid biopsy and microbiome to identify noninvasive biomarkers to diagnose and predict kidney injury and guide ICI therapy.